Application issues of compulsory conciliation in the settlement of fishery disputes in the Yellow Sea - Pan, Xiaolin (Frontiers in Marine Science, 2023)
China and South Korea have made a lot of efforts to settle their fisheries disputes in the Yellow Sea through political negotiations. Expecting for the bilateral treaty concluded around 2001, very limited outcomes have been achieved so far. The procedure of compulsory conciliation in the Law of the Sea can become one alternative choice for two countries to settle the fisheries disputes. This article starts from comparative study among fisheries disputes in the Yellow Sea and those should be subject to compulsory conciliation. Based on the similarities among these disputes, it is argued that compulsory conciliation is applicable in the settlement of the fisheries disputes in the Yellow Sea. This article also pays attention on some essential issues related to the application of compulsory conciliation, including the jurisdiction and authorities of conciliation commission, and the implementation of the report concluded by conciliation commission.